Evaluation of Bian Que Flying Rescue system in rescue and emergency care of acute stroke patients (“扁鹊飞救”系统在脑卒中患者急诊救治中的应用) - MA Hong (马红); OU Lianhua (偶莲花) (中西医结合护理)
Objective To evaluate the Bian Que Flying Rescue system in rescue and emergency care of acute stroke patients. Methods Totally 160 acute stroke patients were divided into the control group (n=80) and observation group (n=80) according to hospital admission sequence. Routine pre-hospital and in-hospital rescue plan was adopted for patients in the control group, and a modified rescue plan based on the Bian Que Flying Rescue system was used for patients in the observation group. The Call to Needle Time, Reception to CT Diagnosis time, Door-to-Needle Time(DNT), Onset-to-Treatment time(OTT) and time to the clinical ward were recorded and compared between two groups. The rate of thrombolytic therapy within 60 min and Spontaneous Intracerebral Hemorrhage(sICH) in 24 h were observed . Results The Call to Needle Time, Reception to CT Diagnosis time, Door-to-Needle Time(DNT), Onset-to-Treatment time(OTT) and time to the clinical ward in the observation group were shorter than those in the control group respectively (P＜0. 01). The rate of thrombolytic therapy within 60 min in the observation group was higher than that in the control group (P＜0. 05). No sICH was happened in either group. Conclusion TheBian Que Flying Rescue system is effective to shorten the emergency response duration and DNT in the rescue and emergency care of acute stroke patients (目的 探讨“扁鹊飞救”系统在脑卒中患者急诊救治中的应用效果。方法 选取2018年11月—2022年12月医院急诊科收治的160例脑卒中患者为研究对象。按照入院先后顺序分为对照组和观察组, 各80例, 对照组采用常规院前及院内急救方案, 观察组实施基于“扁鹊飞救”系统的急性脑卒中救治方案。收集两组患者一般资料, 统计患者救治过程中呼叫“120”至静脉溶栓时间、接诊到CT确诊时间、入院到开始静脉溶栓时间(DNT)、发病至治疗时间(OTT)、入住专科治疗时间等多个关键时间段, 统计患者入院后60 min溶栓率和24 h内症状性颅内出血(sICH)发生情况。结果 观察组患者呼叫“120”至静脉溶栓时间、接诊到CT确诊时间、入院到开始静脉溶栓时间(DNT)、发病到专科治疗时间(OTT)、入住专科治疗时间均较对照组缩短, 差异有统计学意义(P＜0. 01)。观察组60 min溶栓率高于对照组(P＜0. 05), 两组均无24 h内sICH发生。结论 在急诊卒中中心应用“扁鹊飞救”系统, 能有效缩短急救反应时间及患者静脉溶栓时间, 使急诊脑卒中患者急救流程更完善、更快捷。)